Adherence to Radiotherapy in the Treatment of Cancer Patients: A Tertiary Care Institute Experience at Punjab - Singh, Karuna; Singh, Eastpal; Rana, Manjit Kaur; Sharma, Pardeep; Sachdeva, Sheetal (Asian Pacific Journal of Cancer Care, 2022)
Aim: The present study was carried out to analyse the incidence of non-adherence to the radiotherapy treatment and study the factors associated with non- adherence. Patient and methods: The retrospective study was conducted at a tertiary cancer care institute, Punjab. All the patients treated during one year with curative intent with conventional fractionation were included. Incidence of non-adherence was driven and the various parameters like age, gender, site of tumor, stage of disease, intent of treatment, distance from the treating institute, financial constraints were analysed. Results: A total of 660 patients were taken. 6 out of 660 did not come for treatment initiation, hence 654 patients were eligible to be studied. The cumulative incidence of non -adherence was 12.8% (84 out of 654). The majority of patients were of head and neck 31 (36.9%), Elderly >60 years 27 (32.1%), Stage IV 42 (50 %), patients residing in more than 50 km from the institute 47 (55.9%), concurrent chemotherapy 71 (84%), the a major proportion of patient had more than 1 week gap 54 (64%) with 25 (29%) having more than 2 weeks gap. The factors found to be associated with non- adherence was elderly age (p value 0.06), advanced stage (p value 0.003), use of concurrent chemotherapy (p value 0.001), distance from the institute (p value 0.03), treatment with radical intent (p value < 0.001), patients utilizing various government schemes (p value 0.004). No significant association was found between the gender and site of the tumor (p value 0.17 and 0.14 respectively) with the non -adherence. Conclusions: The factors associated were stage of disease, elderly, concurrent chemotherapy, more distance travelled to reach the institute. Non adherence needs to be addressed by proper counselling of patients at the first visit to hospital itself. After the 3 week of radiotherapy treatment patient needs to be seen and followed more frequently when chances skipping treatment are high.